GANGGUAN CAMPURAN CEMAS DAN DEPRESI PADA PASIEN PEMFIGUS FOLIACEUS: LAPORAN KASUS DENGAN PENDEKATAN PSIKIATRI LIAISON - Kosim, Hartono; Wardani, Ida Aju Kusuma; Ariani, Ni Ketut Putri; Mahardika, I Komang Ana (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Pemphigus foliaceus is a chronic autoimmune disease that attacks the superficial layers of the epidermis, causing painful and aesthetically disturbing skin lesions. In addition to physical impacts, this disease can also trigger psychological disorders such as mixed anxiety and depressive disorders, which are often unrecognized by medical personnel. This report discusses the case of a 45-year-old female patient with active pemphigus foliaceus, who presented with complaints of excessive anxiety, depressed mood, insomnia, and decreased social function. The diagnosis was made as mixed anxiety and depressive disorder (F41.2, PPDGJ III). The Consultation-Liaison Psychiatry (CLP) approach was applied, including pharmacological interventions in the form of selective serotonin reuptake inhibitors (SSRIs) and benzodiazepines, as well as non-pharmacological interventions such as supportive psychotherapy, relaxation techniques, and psychoeducation. The CLP approach emphasizes collaboration between dermatologists and psychiatrists for comprehensive treatment. This multidisciplinary management has been proven effective in improving the clinical prognosis and quality of life of patients with dermatological and psychiatric comorbidities. Early detection and integration of mental health services are essential for optimal therapy outcomes. ABSTRAKPemfigus foliaceus merupakan penyakit autoimun kronis yang menyerang lapisan superfisial epidermis, menyebabkan lesi kulit yang nyeri dan mengganggu penampilan. Selain dampak fisik, penyakit ini juga dapat memicu gangguan psikologis seperti gangguan campuran cemas dan depresi, yang sering tidak dikenali oleh tenaga medis. Laporan ini membahas kasus seorang pasien perempuan berusia 45 tahun dengan pemfigus foliaceus aktif, yang datang dengan keluhan cemas berlebihan, suasana hati depresif, insomnia, serta penurunan fungsi sosial. Diagnosis ditegakkan sebagai gangguan campuran cemas dan depresi (F41.2, PPDGJ III). Pendekatan Consultation-Liaison Psychiatry (CLP) diterapkan, mencakup intervensi farmakologis berupa selective serotonin reuptake inhibitor (SSRI) dan benzodiazepin, serta intervensi nonfarmakologis seperti psikoterapi suportif, teknik relaksasi, dan psikoedukasi. Pendekatan CLP menekankan kolaborasi antara spesialis dermatologi dan psikiatri untuk penanganan komprehensif. Penatalaksanaan multidisipliner ini terbukti efektif dalam meningkatkan prognosis klinis dan kualitas hidup pasien dengan komorbiditas dermatologis dan psikiatris. Deteksi dini dan integrasi layanan kesehatan jiwa sangat penting untuk hasil terapi yang optimal.